Winning the battle of intestinal peace with Bacillus—a multifaceted approach to animal health, immunity, and future applications in monogastric livestock production - Vieco-Saiz, Nuria; Lemâle, Olga; Evans, Nicholas P.; Quinteiro-Filho, Wanderley M.; Mellouk, Amine; Consuegra, Jessika; Yakout, Haitham; Goossens, Tim (Frontiers in Microbiology, 2025)
This review focuses on the application of Bacillus-based probiotics in livestock production, emphasizing their potential to enhance animal health, growth performance, and welfare through modulation of the gut microbiota, immune function, and nutrient absorption. Bacillus probiotics, particularly spore-forming strains, offer advantages such as stability during feed processing or the ability to survive gastrointestinal conditions, germinate and produce beneficial metabolites in the intestine. The mechanisms by which Bacillus probiotics exert their effects include influencing microbial communities, producing bioactive compounds, and strengthening gut barrier integrity, which together lead to improved digestive health and resistance to pathogens. Additionally, the challenges in standardizing their effects and identifying reliable biomarkers for evaluating probiotic efficacy or the axes with other organs are highlighted. Overall, Bacillus probiotics are seen as promising, sustainable alternatives to antibiotics with significant potential for future research to optimize their use and understand their mechanisms within the context of animal production and health.